PHYTOCHEMICAL ANALYSIS OF CERTAIN TRADITIONAL MEDICINAL PLANTS - SUMATHI. P,; ISABELLA ROSALINE. S, (International Journal of Pharma and Bio Sciences, 2013)
The traditional medicine involves the use of different plant extracts or the bioactive constituents. For this study, nine medicinal plants such as Andrographis paniculata, Bixa orellana, Catharanthus roseus, Curcuma longa, Ocimum sanctum, Phyllanthus niruri, Terminalis bellerica, Terminalua chebula and Tinospora cordifolia, were subjected to phytochemical analysis employing standard methods. The study confirms the presence of various phytochemicals like Alkaloids, Flavonoids, Saponins, Glycosides, Phenols, Proteins, Steroids, Terpenoids and Tannins. The results obtained in the present study suggest that these plants could be used for curing various ailments and possess potential antioxidant properties and can be used for the isolation of new and novel bioactive compounds.